3y=36-6y

Simple and best practice solution for 3y=36-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y=36-6y equation:



3y=36-6y
We move all terms to the left:
3y-(36-6y)=0
We add all the numbers together, and all the variables
3y-(-6y+36)=0
We get rid of parentheses
3y+6y-36=0
We add all the numbers together, and all the variables
9y-36=0
We move all terms containing y to the left, all other terms to the right
9y=36
y=36/9
y=4

See similar equations:

| t+1/2t-1=5/7 | | 35x+25=140x+175 | | 5y+3=5(4)-2(1) | | y/5+8=24 | | 12x-4=3x-2+6x | | 20x+60=40x+80 | | 100+x/5=-10x+-10x-1 | | -19+12x-10x=-18 | | 7.1x-4.7=62.3 | | (3x+8)^2=64 | | 28–x=3x | | .9(90)=20+16p | | 6x+1/2x+(-1/2)=-(1/2) | | 20+16p=81 | | 12x-34=8x+15 | | -5=n/3 | | (3x+8)2^=64 | | 2x+9+3x+3x=3x+1 | | 2x+9+3x+3x=2x+8 | | 2x+9+3x+3x=2x+7 | | 2x+9+3x+3x=2x+6 | | 2x+9+3x+3x=2x+5 | | 2x+9+3x+3x=2x+4 | | 2x+9+3x+3x=2x+3 | | 2x+9+3x+3x=2x+2 | | 2x+9+3x+3x=2x+1 | | 2x+9+3x+3x=1x+9 | | 2x+9+3x+3x=1x+8 | | 2x+9+3x+3x=1x+7 | | 2x+9+3x+3x=1x+6 | | 2x+9+3x+3x=1x+5 | | 2x+9+3x+3x=1x+3 |

Equations solver categories